An analysis of 12-hour ultramarathon performance - Knechtle, Beat; Villiger, Elias; Valero, David; Weiss, Katja; Vancini, Rodrigo Luiz; Nikolaidis, Pantelis Theo; Scheer, Volker; Rosemann, Thomas; Thuany, Mabliny (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Ultra-marathon running is highly popular, with races including distance-limited, time-limited, and multistage events. The 12-hour run is the second shortest time-limited ultra-marathon, though little is known about the origin of athletes or where these races are preferably held. Therefore, the present study investigated where the fastest 12-hour runners originate from and where the fastest 12-hour race courses are located.Methods. A machine learning model based on the XG Boost algorithm was developed to predict running speed based on athlete age, sex, country of origin, and the country where the races were held. After the model was built and trained, explain-ability tools were used to investigate how each independent variable influenced the predicted running speed.Results. A total of 103,334 race records of 53,700 unique runners from 69 countries participating in races held in 55 coun-tries were analysed. The United States of America (USA) accounted for about one-third of the 12-hour race records for country of origin and country of the event, followed by Taiwan, several European countries (e.g., Germany, France, Italy, and Norway), and others from the Anglosphere (e.g., Australia, United Kingdom, and South Africa). Athletes from Lithuania, Israel, Russia, Hungary, Croatia, and Namibia achieved the fastest average running speeds. The fastest running speeds were achieved in races held in Russia, the Netherlands, Israel, Slovakia, the Czech Republic, Croatia, and Hungary. There was a positive correlation between country of origin and country of event, indicating that athletes competed mainly in their home country. Men were about 0.5 km/h faster than women on average. Most athletes were in the 45–49 age group, while the fastest run-ners were in the 40–44 and 45–49 age groups.Conclusions. Most 12-hour ultra-marathon athletes originated from the USA and competed in the USA. However, athletes from Lithuania, Israel, Russia, Hungary, Croatia, and Namibia achieved the fastest running speeds.
Keywords: ultra-endurance; ultra-marathon; ultra-running; event location; origin; country